2016
DOI: 10.18632/oncotarget.11118
|View full text |Cite
|
Sign up to set email alerts
|

TIMP-1 is under regulation of the EGF signaling axis and promotes an aggressive phenotype in KRAS-mutated colorectal cancer cells: A potential novel approach to the treatment of metastatic colorectal cancer

Abstract: It is now widely accepted that therapeutic antibodies targeting epidermal growth factor receptor (EGFR) can have efficacy in KRAS wild-type advanced colorectal cancer (CRC) patients. What remains to be ascertained is whether a subgroup of KRAS-mutated CRC patients might not also derive benefit from EGFR inhibitors. Metalloproteinase inhibitor 1 (TIMP-1) is a pleiotropic factor predictive of survival outcome of CRC patients. Levels of TIMP-1 were measured in pre-treatment plasma samples (n = 426) of metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…MMP-14, on the other hand, degrades other basement membrane components, such as collagen type I [14]. TIMP-1, associated with MMPs, has been described as a predictive factor of survival and might predict recurrence in certain types of cancer [15,16]. In contrast, TIMP-2 is the only TIMP protein that can inhibit the mitogenic response independently of MMP [17].…”
Section: Introductionmentioning
confidence: 99%
“…MMP-14, on the other hand, degrades other basement membrane components, such as collagen type I [14]. TIMP-1, associated with MMPs, has been described as a predictive factor of survival and might predict recurrence in certain types of cancer [15,16]. In contrast, TIMP-2 is the only TIMP protein that can inhibit the mitogenic response independently of MMP [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found that TIMP‐1 plasma levels predicted benefit from EGFR‐inhibition therapy in KRAS ‐mutated metastatic colorectal cancer patients. These results were supported by data from cellular models showing that exposure of colorectal cancer (CRC) cells to exogenously added recombinant TIMP‐1 promoted a more aggressive behavior in these cells, specifically in KRAS ‐mutated cells (Tarpgaard et al , ). We added recombinant TIMP‐1 to a matched set of isogenic DLD‐1 CRC cell clones, in which either the endogenous KRAS wt allele (from here on referred to as DLD‐1 G13D cell line) or the KRAS (G13D) mutant allele (from here on referred to as DLD‐1 wt cell line) has been inactivated by targeted homologous recombination (Yun et al , ), respectively.…”
Section: Introductionmentioning
confidence: 79%
“…Although TIMP‐1 expression is up‐regulated in colorectal tumor tissue (Lu et al , ), the molecular mechanisms underlying the prognostic effect of TIMP‐1 in CRC remain unclear. We previously reported a differential cellular effect of TIMP‐1 on CRC cell invasion, dependent on KRAS status (Tarpgaard et al , ). A similar observation has also been reported for pancreatic ductal adenocarcinoma, where exogenous addition of human recombinant TIMP‐1 significantly increased proliferation of pancreatic ductal cells, but only in KRAS ‐transformed cells (Botta et al , ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As such, inhibitors of the EGFR signaling pathway have received attention as potential therapeutic agents (49). Moreover, EGF-induced activation of EGFR increases MMP-9 expression levels through the activation of the PI3K/Akt pathway in patients with glioblastoma (50).…”
Section: Discussionmentioning
confidence: 99%